Reforma al artículo 4 de la ley orgánica para la promoción del trabajo juvenil, regulación excepcional de la jornada de trabajo, cesantía y seguro de desempleo, para garantizar la intangibilidad de la remuneración y de la jornada laboral - Cañart Alvarado, Diego Fernando (2017)
The matrix problem generated after the process of analysis and deduction prior recognition of the techniques and procedures of a legal investigation of applied character, focuses on the review and theoretical study of important institutions and legal figures of relevant connotation in the area of positive law; The problem object of study is limited to the treatment of the Organic Law for the promotion of the youth work, exceptional regulation of the working day, unemployment and unemployment insurance, body of rules in force since 28 March of the year 2016 from its publication in the official register this legislation has generated changes in the dynamics of the labor market in Ecuador, so it is important to the thorough review of New legal framework by law professionals, students and society in general; in such a manner as to imply a priority for the future lawyer as well as for the professional in free exercise, review and critical study of the reforms in the aforementioned law. The Organic Law for the promotion of the youth work, exceptional regulation of the working day, unemployment and unemployment insurance, has generated a broad debate by substantial changes not only in the labor code, but also in the organic law of the public service and in the social security act, a situation that has generated discussion within the legal forum by the socio-economic effects. In other words the limitation of the right to remuneration, as well as the inviolability of the length of the working day, as standard the article transcribed, has involved an obvious injury to the worker and his family, generating in addition some as well as the growth in the gap between the worker and the employer who has not exactly been rectified with the reforms raised by the law relating to the review. The decrease in the percentage of the remuneration they receive workers within the private sector does not produce employment benefits of any kind, on the contrary, it has a significant negative effect on workers, they have been undermined a right historically recognized, which represents a step backward in the area of recognition of labor rights and a clear contrast to the labor principles provided in the Constitution of the Republic and in the international human rights instruments. With this background, it is necessary to base in concrete form a reform proposal to Art. 4 of the Organic Law for the promotion of the youth work, exceptional regulation of the working day, unemployment and unemployment insurance, to repeal expressly to this limitation on the right to the inviolability of the remuneration.